1972
DOI: 10.1002/ar.1091740405
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hyperthyroidism on the fine structure of the zona fasciculata of the rat adrenal cortex

Abstract: Chronic hyperthyroidism was induced in radiothyroidectomized and surgically thyroidectomized adult male rats by feeding a diet of 0 3 4 . 4 % desiccated thyroid for four to ten week periods. Short term hyperthyroidism was induced in intact rats by the intraperitoneal injection of 250 pg/day of sodium levothyroxine for ten days. Adrenal glands were fixed by perfusion with 3% phosphate buffered glutaraldehyde and post-fixed in 1 % osmium tetroxide. The zona fasciculata of the adrenal glands from experimental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, symmetrical enlargement of the adrenals in the context of hypercortisolism has almost always been associated with physiological contexts in which there has been hyperstimulation of the adrenal cortex with ACTH, rather than with the context of a primary adrenal process (8,18,19). In light of our previous oCRH stimulation studies, this would suggest a central locus for the hyperthyroid-mediated hypercortisolism.…”
Section: Discussionmentioning
confidence: 93%
“…However, symmetrical enlargement of the adrenals in the context of hypercortisolism has almost always been associated with physiological contexts in which there has been hyperstimulation of the adrenal cortex with ACTH, rather than with the context of a primary adrenal process (8,18,19). In light of our previous oCRH stimulation studies, this would suggest a central locus for the hyperthyroid-mediated hypercortisolism.…”
Section: Discussionmentioning
confidence: 93%
“…The significant reduction in adrenal weight seen in hypothyroid rats is also compatible with either primary or secondary adrenal insufficiency and is almost never seen in any other context (33). However, symmetrical enlargement of the adrenals in the context of hypercortisolism has almost always been associated with physiological contexts in which there has been hyperstimulation of the adrenal cortex with ACTH, rather than with the context of a primary adrenal process (33,35,36). Although we cannot definitively document the cause of the subtle adrenal insufficiency seen in our hypothyroid rats, this adrenal insufficiency does not seem to reflect the reduction in corticosterone clearance known to occur in hypothyroidism or the reduced CBG-binding capacity seen in the present study of hypothyroid rats.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have been reported following the administration of adrenal hormones (DeLemos et al, 1970;Kotas and Avery, 1971; Picken et al, 1974). Since effects of adrenal hormones on the thyroid gland (Solis-Cohen, 1897; Marine, 1930;Malendowicz and Filipiak, 1975), and of thyroid hormone on the adrenal glands (Hoskins, 1910;Steinetz and Beach, 1963;DAngelo and Grodin, 1964; Moore and Callas, 1972), are well established, consideration must be given to the possibility that the lung effects produced by thyroid administration may be mediated through activity of the adrenal cortex. To date, no studies have been reported investigating adrenal activity or thyroid-adrenal interactions influencing the thyroid-induced changes described in mature lung.…”
mentioning
confidence: 99%